Attentional Bias in Older Adults with Non-Clinical Depression: An Eye-Tracking Study. - Yuan, Jing; Chen, Yina; Yuan, Xinyi; Zhang, Yuchen; Wang, Yan; Liu, Zejun (Experimental Aging Research)
Background: Cognitive models of depression assert that attentional biases play an important role in the maintenance of depression. However, few studies have explored attentional bias in depressed older adults, and no consistent conclusions have been reached. Methods: In the current study, we investigated attentional bias in older adults with non-clinical depression. Older adults aged over 60 with non-clinical depression and without depression were instructed to perform a free viewing task while their eye movements were tracked. Results: The results showed that, compared to older adults without depression, non-clinically depressed older adults had longer total fixation durations and a greater number of fixations on sad stimuli. Moreover, non-depressed older adults exhibited a preference for pleasant images, whereas this effect was not observed in older adults with non-clinical depression. Conclusion: This study suggested that non-clinically depressed older adults have attentional bias, which is manifested as increased attention to sad stimuli and decreased attention to pleasant stimuli.The current study has functional and potential functional implications.